1997
DOI: 10.1111/j.1475-2743.1997.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vegetation species and plant properties on runoff and soil erosion: results from a rainfall simulation study in south east Spain

Abstract: Abstract. To study the influence of different vegetation species and plant properties on the generation of surface runoff and soil erosion in south east Spain, a series of rainfall simulation experiments was conducted on small (c. 1.5 m2) plots. These were carried out in October 1993 and May 1994 on two sites close to Murcia. Six vegetation types were studied, with some at different stages of maturity, giving a total of nine vegetation treatments and two bare soil treatments. Four replicates of each treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 7 publications
1
75
0
5
Order By: Relevance
“…En el caso que nos ocupa, la vegetación, su grado de cobertura y composición del estrato es el principal factor diferenciador de las tres zonas. Los resultados obtenidos confirman la importancia de la existencia o ausencia de una cubierta vegetal en la respuesta hidrológica de las zonas semiáridas (Wilcox et al, 1988;Castillo et al, 1997;Quinton et al, 1997).…”
Section: Figura 2 Detalle De La Instrumentalización De Las Cuencasunclassified
“…En el caso que nos ocupa, la vegetación, su grado de cobertura y composición del estrato es el principal factor diferenciador de las tres zonas. Los resultados obtenidos confirman la importancia de la existencia o ausencia de una cubierta vegetal en la respuesta hidrológica de las zonas semiáridas (Wilcox et al, 1988;Castillo et al, 1997;Quinton et al, 1997).…”
Section: Figura 2 Detalle De La Instrumentalización De Las Cuencasunclassified
“…This flexibility makes barley a good NO 3 -catch crop because its growth is adapted to the soil N availability. Nevertheless, if the goal is to reach ground cover > 70% to control soil erosion (Quinton et al 1997), vetch seems to be a better fit when low residual N is left after the main crop. Cereal-legume mixtures are likely a good solution, combining the quick initial growth of the grass with the ground cover provided by vetch in winter (Alonso-Ayuso et al 2014).…”
Section: Cover Crops: Biomass N Content and N Uptakementioning
confidence: 99%
“…Soil erosion and sediment transport are therefore decreased through decreasing surface runoff and increasing water infiltration into the soil (Colman, 1953;Morgan, 1986;Sahin and Hall, 1996;Castillo et al, 1997;Quinton et al, 1997). Huang and Zhang (2004), Mu et al (2007), and Zhang et al (2008) found that changes in streamflow tended to be relatively uniform across the flow spectrum with typical reductions of 30-60 % in catchments in the region due to soil conservation measures.…”
Section: Introductionmentioning
confidence: 99%